Graphene delamination from chemical vapor deposited turbostratic multilayer graphene for TEM analysis. (29th January 2023) - Hayashi, Kenjiro; Fushimi, Naoki; Kataoka, Masako; Kondo, Daiyu; Sato, Shintaro
Abstract: Turbostratic multilayer graphene (MLG) is of great interest due to its unique electronic properties resulting from a linear band dispersion at the K point, which is similar to that of single-layer graphene. The band structure is derived from the stacking structure of turbostratic MLG where graphene layers have random in-plane rotations with respect to each other. Although wafer-scale growth of turbostratic MLG has been demonstrated, the crystallinity of individual graphene layers is still challenging to investigate. In this study, we present a new approach to reveal the grain structure of turbostratic MLG by transmission electron microscopy (TEM) observation. Mechanical delamination is demonstrated for the chemical vapor deposited MLG to peel off the topmost graphene layers by using a polydimethylsiloxane sheet. Micrometer-scale patterning of the MLG prior to the delamination is found to be effective to obtain graphene films with the designed shape and arrangement. Furthermore, the delaminated graphene films are successfully transferred onto a TEM grid, enabling us to estimate the grain size of the turbostratic MLG. This method is potentially applicable for not only preparing samples but also fabricating vertically stacked heterostructure devices using 2D materials.